On the Presence of Speculative Bubbles in Stock Prices - Dezhbakhsh, Hashem; Demirguc-Kunt, Asli (Journal of Financial and Quantitative Analysis, 1990)
We examine empirically the existence of speculative bubbles in U.S. stock prices and, by building on West's procedure, propose direct and computationally simple tests of the “nobubble” hypothesis. These tests are likely to be close to their nominal size in small samples and to have small sample power against a wide class of bubbles including those orthogonal to the dividend process. We apply the tests to long-term annual U.S. stock market data for the 1871–1981 and 1871–1988 periods. Contrary to West, we do not reject the “no-bubble” hypothesis. We offer an explanation as to the cause of discrepancy between the two results.